The Effects of Well-Being and Work Motivation on Service Quality: The Mediating Role of Job Satisfaction - Musahadatus Sifa; Muafi Muafi; Faizal Madya (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: The purpose of this study is to examine and analyse the effect of well-being and work motivation on employee service quality with the mediating role of employee job satisfaction in the Dinas Pendidikan, Pemuda, dan Olahraga (DINDIKPORA) Rembang Regency Methodology/approach: This study uses a quantitative approach with latent variable model analysis on 122 employees of the DINDIKPORA Rembang Regency Results: Well-being positively affects service quality (p=0.000; ?=0.408), and work motivation also positively affects service quality (p=0.000; ?=0.408). Well-being (p=0.000; ?=0.465) and work motivation (p=0.000; ?=0.498) both positively affect job satisfaction. However, job satisfaction does not affect service quality (p=0.140; ?=0.138) and does not mediate the effect of well-being on service quality (p=0.165; ?=0.064) and the effect of work motivation on service quality (p=0.162; ?=0.069). Conclusions: Well-being and work motivation improve service quality and job satisfaction. However, job satisfaction does not affect service quality and, therefore, cannot act as a mediator. Limitations: This study was limited to non-teaching staff at DINDIKPORA Rembang and did not cover other relevant variables. The results show that 47.5% of service quality is influenced by the research variables, whereas the remaining 52.5% is influenced by other factors. Contributions: This study shows that service quality in public organizations is more influenced by well-being and work motivation than job satisfaction, and provides managerial implications for the DINDIKPORA Rembang Regency